Multiple simultaneous hypertensive supratentorial and infratentorial hemorrhages: A rare kind of hypertensive bleed - Lamichhane, D; Paudel, R (Journal of College of Medical Sciences-Nepal, 2012)
Multiple simultaneous intracranial hemorrhages are very uncommon and both supra- and infratentorial hemorrhages are even more rare. Here we report a case of 56 year old hypertensive male with no other significant medical history who presented with a hypertensive emergency. Emergency head computed tomography showed bilateral basal ganglia and midbrain hemorrhages extending to right cerebellar peduncle. The patient made a progressive recovery and finally achieved functional independence. This report shows that hypertension may cause multiple simultaneous supra- and infratentorial hemorrhages and have good prognosis. Journal of College of Medical Sciences-Nepal,2011,Vol-6,No-4, 53-56 DOI: http://dx.doi.org/10.3126/jcmsn.v6i4.6728